2018
DOI: 10.1021/acs.nanolett.8b01421
|View full text |Cite
|
Sign up to set email alerts
|

PVDF/Palygorskite Nanowire Composite Electrolyte for 4 V Rechargeable Lithium Batteries with High Energy Density

Abstract: Solid electrolytes are crucial for the development of solid state batteries. Among different types of solid electrolytes, poly(ethylene oxide) (PEO)-based polymer electrolytes have attracted extensive attention owing to their excellent flexibility and easiness for processing. However, their relatively low ionic conductivities and electrochemical instability above 4 V limit their applications in batteries with high energy density. Herein, we prepared poly(vinylidene fluoride) (PVDF) polymer electrolytes with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
200
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(201 citation statements)
references
References 51 publications
1
200
0
Order By: Relevance
“…The Li 2 SO 4 ‐doped SiO 2 CPEs demonstrates lower E a values than that of the Li 2 SO 4 ‐free one, indicating improved Li + conduction behaviors by Li‐salt introducing. The Li + transference number ( t Li+ ) of the SiO 2 /Li 2 SO 4 /PEO CPEs was evaluated by the potentiostatic polarization (PP) method . As shown in Figure S9 (Supporting Information), the Li 2 SO 4 ‐doped SiO 2 CPEs yield higher t Li+ values (0.25, 0.32, 0.45, and 0.52 for 0, 0.05, 0.10, and 0.15 g Li 2 SO 4 , respectively) than the reported bare PEO/LiTFSI electrolyte (0.12) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Li 2 SO 4 ‐doped SiO 2 CPEs demonstrates lower E a values than that of the Li 2 SO 4 ‐free one, indicating improved Li + conduction behaviors by Li‐salt introducing. The Li + transference number ( t Li+ ) of the SiO 2 /Li 2 SO 4 /PEO CPEs was evaluated by the potentiostatic polarization (PP) method . As shown in Figure S9 (Supporting Information), the Li 2 SO 4 ‐doped SiO 2 CPEs yield higher t Li+ values (0.25, 0.32, 0.45, and 0.52 for 0, 0.05, 0.10, and 0.15 g Li 2 SO 4 , respectively) than the reported bare PEO/LiTFSI electrolyte (0.12) .…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced t Li+ could be assigned to two reasons. First, the incorporating of mesoporous SiO 2 /Li 2 SO 4 nanofibers into the PEO/LiTFSI matrix, promotes the anions absorption and relaxation of polymer local chains for more free Li + ; second, in situ introduced Li salt within the nanofibers affords considerable intrinsic Li + conduction. Besides, time‐related ionic conduction was investigated to determine the composite electrolyte stability over duration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 According to the previous reports, various structures of PVDF and its copolymers have been developed, including fiber arrays, nanowires, thin film, and nanotube arrays. [55][56][57][58][59][60] Thin film poly(vinylidene fluoride-co-trifluoroethylene) (P[VDF-TrFE]) owns a significant value for large-area deposition, excellent uniformity, and remarkable surface morphology. 61 However, the piezoelectric constant of the fiberbased composites exhibits about four times greater than the controlled thin film-based ones.…”
Section: Piezoelectric Materials and Structural Designmentioning
confidence: 99%
“…As mentioned above, these liquid organics were also termed as plasticizers. For example, Yang and co‐workers investigated the influence of the content of DMF solvent residue in PVDF‐based composite solid electrolyte on the ionic conductivity. They observed that the ionic conductivity increased with the increment of DMF residue by adjusting the vacuum‐dried temperature.…”
Section: Overview Of Polymer Matrices and Inorganic Fillersmentioning
confidence: 99%